Intrathecal Infusions for Intractable Cancer Pain: A Qualitative Study of the Impact on a Case Series of Patients and Caregivers - Philippa Hawley; Elizabeth Beddard-Huber; Cameron Grose; William McDonald; Daphne Lobb; Louise Malysh (Pain Research and Management)
BACKGROUND: The need for intrathecal infusion in a palliative care setting is infrequent. Despite established efficacy, safety and cost effectiveness, this is considered an ‘extraordinary measure’ in Canada. Patients requiring this approach are not typical palliative care patients, having shorter and more uncertain life expectancies.